FEATURES OF TRACE ELEMENT COMPOSITION OF BERYL FROM THE URALIAN IZUMRUDNYE KOPI - A.K. Gavrilchik; S.G. Skublov; E.L. Kotova (Минералогия)
It was found as a result of SIMS study of beryl with various color zoning from the Uralian Izumrudnye Kopi that the content of a number of trace elements regularly varies to the margin of the crystal regardless of the color nature of the central and marginal crystal parts. The Na, Mn, Ga, Fe and Rb content increases towards the periphery of both crystals forming a U-shaped zoning. This pattern is less pronounced for Ni and Co. The Ti content, on the contrary, decreases towards the crystal margin forming a bell-shaped zoning. The distribution of a number of elements demonstrates another zoning pattern. For the beryl crystal (sample 24), the color saturation and transparency of which increases from a colorless to green-yellow from the center to the periphery of the crystal, the Sc, Cr and V forms U-shaped zoning with an increasing content to the margin of the crystal and Li exhibits a bell-shaped zoning. In transparent beryl crystal with more intense green color in the center (sample 25), the zoning pattern is dramatically distinct: bell-shaped for Sc, Cr and V and U-shaped for Li. The content of each element for both crystals coincides in the marginal zones, which have color comparable in intensity and transparency, in spite of different color pattern with a strongly contrasting distribution in the central part. In discriminant diagrams for the identification of emeralds from various world regions, the composition of beryl from the Uralian Izumrudnye Kopi correspond to the field of compositions of the Uralian emeralds or is close to them.